Comparative assessment and safety issues in state-of-the-art hydrogen production technologies. (9th November 2016) - Guandalini, Giulio; Campanari, Stefano; Valenti, Gianluca
Abstract: This work discusses the development of a benchmark comparison among hydrogen production technologies, focussing on the assessment of their operating conditions by the point of view of the potential impact on safety. The analysis focuses on state-of-the-art, fully industrialized and commercial technologies, or at least with established early-market availability, not considering unconventional or emerging technologies still featuring a low technology readiness level. After a selection of hydrogen production technologies and their classification according to the possible feedstock, hydrogen purity and plant size, operating conditions and relative component sizes were calculated. Temperatures, pressures and chemical features are given in the most important points, as well as relative size of components, considering that these factors can be important by the point of view of safety. The qualitative comparison of the investigated technologies evidenced the presence of flammable and toxic mixtures at high temperature common to all the natural gas fed technologies, while gasifiers generally operates at lower temperature. ATR and gasifiers exhibit flammable and toxic gases at high pressure, as well as highly reactive streams (i.e. pure oxygen). This last is an aspect common also to electrolysis and POX. Common ranges for operating conditions are provided as a support for subsequent safety evaluation on how critical is a certain plant by the point of view of safety. Highlights: Comparative assessment of operating condition in hydrogen production plants. Benchmark of commercial hydrogen production pathways characteristics. Plant layout with operating conditions in relevant points and qualitative sizing. Connection with safety issues in commercial plants (flammable, toxic, caustic).